INFLUENCE THE IMPLEMENTATION OF FINANCIAL MANAGEMENT POLICIES OF PRIVATE UNIVERSITIES TO IMPROVE FINANCIAL MANAGEMENT IN EDUCATION FUNDING TO PAY STUDENTS' PARTICIPATION IN STIKES KARSA HUSADA GARUT REGENCY - Perceka, Andhika Lungguh; Melliasany, Novie (Universitas Negeri Yogyakarta, 2022)
Education funds derived from student participation is one of the main sources of funding education in private universities. Utilization of education funds for the benefit of students will be determined by sound financial management and planning. This study aims to explore, uncover and analyze the effect of the influence of the implementation of financial management policies of private colleges to financial management in an effort to increase the participation of students in education funds paid in Karsa Husada Of College of Health Science Garut. The method used in this study is a survey method descriptive analysis. The study population comprised 380 people, while the samples in this study were 80 people who were taken on the basis of stratified random sampling technique. While the technical analysis of the data used is the statistical analysis with path analysis. Hypothesis testing results show that the implementation of financial management policies have a positive influence on financial management; financial management policies have a positive influence on student participation in education funds paid; in education funds paid, and impact on improving financial management in education funds to pay student participation.